Faculty Perception of Library Aesthetics and Perceived Need for a Functional Research Commons to Support Scholarly Productivity: A Case Study of Hezekiah Oluwasanmi Library, Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study examined Faculty Perception of Library Aesthetics and Perceived Need for a Functional Research Commons to Support Scholarly Productivity: A Case Study of Hezekiah Oluwasanmi Library, Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria. The study employed descriptive survey research method. A total of 132 faculty lecturers were considered across all the faculties in Obafemi Awolowo University. Questionnaire was used for data collection and 132 self-structured questionnaire was distributed to the lecturers as respondents in the university. 129 (97.73%) questionnaire were received and used as the basis for data analysis. The findings revealed that overall ambience of the library is welcoming and aesthetically pleasing, the furniture in the library is modern, comfortable, and conducive to research. A visually pleasing library environment enhances ability to concentrate on academic tasks and aware about the benefits of a Research Commons among faculty members that a visually pleasing library environment enhances the ability to concentrate on academic tasks and awareness of the benefits of a Research Commons among faculty members that understands how a Research Commons supports collaborative and interdisciplinary research. It was recommended that the university management should invest in sustaining and enhancing the aesthetic appeal of the library. Regular refurbishment, ergonomic furniture, optimized lighting, and clean, orderly spaces can boost scholarly engagement. The university should equally prioritize the functionality of a Research Commons equipped with high-speed internet, collaborative spaces, research software, data analysis tools and digital repositories to support faculty research.